An Effective Dark–Vis–UV Ternary Biomimetic Switching Based on N3/Spiropyran‐Modified Nanochannels. Issue 46 (3rd October 2018) - Zhang, Dan; Wang, Qinqin; Fan, Xia; Zhang, Mingliang; Zhai, Jin; Jiang, Lei
Abstract: Many natural photomodulated nanochannels are investigated and are crucial for biological activity. Biomimetic nanochannels with a bistable conductance state under light stimulus are demonstrated. In this system, two molecules, cis ‐bis‐(4, 4′‐dicarboxy‐2, 2′‐bipyridine) dithiocyanato ruthenium(II) (N3) and spiropyran 1′‐(3‐carboxypropyl)‐3′, 3′‐dimethyl‐6‐nitro‐spiro[2H‐1]benzopyran‐2, 2′‐indoline (SP‐COOH), each with unique photoresponsive properties, are modified in alumina nanochannels. The two segments of the hourglass‐shaped alumina nanochannels are designated to graft a certain molecule. Under ultraviolet (UV) or visible light (vis) irradiation, electrons belonging to N3 are excited, resulting in negatively charged surfaces on the sides of nanochannels modified with N3 molecules. Only under UV stimulus, the conformation change of the SP‐COOH molecules leads to positively charged surfaces of nanochannels in the SP‐COOH occupied sides. Benefiting from the joint effect of N3 and SP‐COOH, low, medium, and high (i.e., "0, " "1, " and "2") ternary levels of ion conductance are established under the dark–vis–UV alternate stimuli. The multistage current switching containing "0‐1‐2‐0" and "0‐1‐2‐1‐0" procedures is stable and robust. Additionally, the diode‐like ion transport behavior of the nanochannels could be exploited to support a multivalued logical gating with the management of light signals. Abstract : A biomimetic dark–vis–UV ternary switching based on N3/SP‐COOH‐modified nanochannels with the cooperative function of photoinduced electron transition in N3 and conformational change from SP‐COOH is developed. Low, medium, and high (i.e., "0, " "1, " and "2") ion current conductances are demonstrated with stable switching cycles of "0‐1‐2‐0" and "0‐1‐2‐1‐0, " which support the construction of a photocontrolled multivalued logical gating.